Tropy cielesności w poezji Anny Frajlich .......... 249 - Bartos, Ewa (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
ON CORPOREAL TROPES IN ANNA FRAJLICH’S POETRYIn Anna Frajlich’s works one can observe a reflection on corporeality. Even though Frajlich does not shy away from describing bodies which are sensual, erotic, and ones that experience emotions, she also pays attention to bodies which suffer and are stricken with pain. “On Corporeal Tropes in Anna Frajlich’s Poetry” is an attempt to take a closer look at the diverse ways in which corporeality is understood by the author of Łodzią jest i jest przystanią.